Images of Change Visual Representations of Papal Power in Rome Following the Council of Trent - Delgado-Jermann, Teresa (Taylor & Francis, 2023)
Images of Change focuses on the visual propaganda employed by Catholic popes in Rome during the time of Tridentine Reform. In 1563, at the Council of Trent, the Catholic Church decided to reform its own use of imagery, in response to Protestant criticism. This volume examines how different sixteenth-century popes dealt with church reform by looking at the variety of artworks that were commissioned particularly in the city of Rome, the immediate sphere of influence of papal power. Based on original research in the Vatican archives, the book argues that because of the contradictory media strategies employed by individual popes, the papacy began to lose its spiritual and temporal influence and power. This book will appeal to students and scholars alike interested in the Roman Catholic Church in and around the sixteenth century, as well as Early Modern religious reform and Papal influence.